A Highly Sensitive and Selective Enzymatic Biosensor Based on Direct Electrochemistry of Hemoglobin at Zinc Oxide Nanoparticles Modified Activated Screen Printed Carbon Electrode. Issue 9 (2nd September 2014) - Palanisamy, Selvakumar; Karuppiah, Chelladurai; Chen, Shen‐Ming; Periakaruppan, Prakash
Abstract A sensitive enzymatic biosensor has been developed for the detection of hydrogen peroxide (H2O2), nitrite (<alternatives> <![CDATA[NO- 2]]> <inline-graphic xlink:href="ark:/27927/pgh18r9kq43" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>) and trichloroacetic acid (TCA) by using hemoglobin (Hb) immobilized on activated screen printed carbon electrode (ASPCE) and zinc oxide (ZnO) composite. A pair of well defined redox peaks is observed with a heterogeneous electron transfer rate constant (Ks) of 5.27 s−1 for Hb at ASPCE/ZnO. The biosensor exhibits the detection of H2O2, TCA and <alternatives> <![CDATA[NO- 2]]> <inline-graphic xlink:href="ark:/27927/pgh18r9kps2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> in the concentration range of 0.5–129.5 µmol L−1, 2.5–72.5 mmol L−1 and 0.2–674 µmol L−1 with the detection limit of 0.083 µmol L−1, 0.12 mmol L−1 and 0.069 µmol L−1, respectively.